Is elastic fantastic? The impact of elastic inserts on rein tension - Randle, H.; Abbey, A. (DCA Report; Nr. 044, 2014)
There is an industry wide interest in developing horse equipment to enhance riding and training practices. Elastic has been used over the years to achieve "give" in and flexibility in equipment such as girths and reins. Sustainable and ethical equitation relies upon the effective delivery and receipt of clear signals and timely pressure-release. This study aimed to determine the effect of elastic insert in reins on first, the tension applied for normal riding and a walk to halt transition, and second, the ability to release the tension in the reins. Thirty regular riders (.4 times/week), all female, average age 22+/-3.87 years, participated in this study. The Centaur Rein Tension GaugeTM was fitted to a fixed structure and reins with elastic insert or standard rubber reins were attached. Both sets of reins measured 20 mm x 6 mm (width x depth) and weighed 350 g. Rein tensions (N) were measured for left and right hands, both rein types when taking up a normal riding contact and executing a walk to halt transition using a cross-over design. The time (s) for a total release of tension was also derived for each rein type. There were three replicates for each rein type. Significantly different tensions were observed between the two types of rein (F1,16=5.54; P<0.05). Lower tensions were exerted with the elastic insert (3.33 +/-1.97N) than with the rigid reins (5.83+/-1.17N) in the normal riding contact condition, whilst higher tensions were evident with elastic insert reins (21.3+/-6.19N) than with rigid reins (15.8+/-4.4N) in the walk to halt transition. The time taken for rein tension to return to zero following complete release from a set value of 25N was significantly greater and less consistent with the elastic insert reins (F1,8=5.05; P<0.05; 3.85+/-3.22s) than with the rigid reins (0.53+/-0.27s). This study suggests that although elastic inserts in reins may result in less tension in general riding, they may alter riders' behaviour in terms of the tension applied when executing a particular equitation task. Furthermore, elastic inserts in reins may have a deleterious effect on a rider's ability to apply negative reinforcement accurately and therefore clarity during training. LP: Rein design which includes elastic can have a substantial impact on the tensions applied particularly when making transitions during equitation. The impaired ability to simultaneously release pressure may have a negative impact on equine learning and training, and consequently equid stress and welfare.